2016
DOI: 10.1038/jp.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Real vs simulated umbilical cords for emergency umbilical catheterization training: a randomized crossover study

Abstract: RC has higher physical and functional fidelity, and are preferred for training by pediatric residents, despite longer placement times.Journal of Perinatology advance online publication, 27 October 2016; doi:10.1038/jp.2016.194.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…We did not measure or compare the time to successful catheter placement for REAL or ART. In a previous study, an umbilical catheterization hybrid model required a longer time to catheter placement compared with a synthetic model . Last, we did not use a previously validated MCQ knowledge test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not measure or compare the time to successful catheter placement for REAL or ART. In a previous study, an umbilical catheterization hybrid model required a longer time to catheter placement compared with a synthetic model . Last, we did not use a previously validated MCQ knowledge test.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, an umbilical catheterization hybrid model required a longer time to catheter placement compared with a synthetic model. 10 Last, we did not use a previously validated MCQ knowledge test. High-stakes MCQ tests require multiple raters and large numbers of participants to assure reliability and validity, and have not been published for umbilical catheterization knowledge assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emergency UVC training can use one of the two types of umbilical cord models: simulated umbilical cord and real umbilical cord. Prior research has shown that emergency UVC training with real umbilical cords has educational advantages for some learners [ 9 ]. In this Technical Report, we describe how to create a real human umbilical cord simulator model for emergency UVC placement training.…”
Section: Introductionmentioning
confidence: 99%